A Study on the Relationship between Employee Engagement and Faculty Retention in Higher Education Institutions - Savita Singh; Dr. Ajit Singh Patel, (International Journal of Management and Humanities (IJMH), 2025)
Employee engagement plays a crucial role in faculty retention within higher education institutions. This study explores the relationship between engagement levels and faculty members' decisions to remain in academic institutions. The study draws on survey responses from faculty members at various universities to assess how engagement influences retention rates. Findings indicate that institutions with higher engagement levels exhibit lower faculty turnover, as engaged faculty members demonstrate increased commitment, productivity, and job satisfaction. The study emphasises the importance of implementing strategic policies that foster engagement through professional development, recognition programs, and supportive leadership. These insights provide valuable recommendations for higher education administrators seeking to promote a stable and motivated faculty workforce.